Understanding Internalizing and Externalizing Behaviors in Autistic Toddlers - Levy, Rachel S; Fipp-Rosenfield, Hannah L; Lee, Jordan P; Grauzer, Jeffrey M; Roberts, Megan Y (American journal of speech-language pathology, 2023)
The majority of autistic toddlers present with clinically significant levels of internalizing or externalizing behaviors. Despite the prevalence of internalizing and externalizing behaviors in caseloads, the overwhelming majority of speech-language pathologists (SLPs) have not received specialized instruction in how to support children with these behaviors. The purpose of this study was to identify which child and caregiver characteristics are most associated with internalizing and externalizing behaviors in autistic toddlers in order to consider how SLPs may tailor their treatment to better support the individual needs of autistic children. Participants included 109 mothers and their autistic children between 18 and 48 months of age. This study was a secondary analysis of data from a randomized clinical trial. Participants' baseline data included a variety of child (i.e., expressive language, receptive language, restricted and repetitive behavior [RRB], and nonverbal cognition) and caregiver (i.e., self-efficacy and responsiveness) characteristics. Seemingly unrelated regressions were conducted to determine which characteristics were associated with internalizing and externalizing behaviors in autistic toddlers. Higher RRB scores were associated with both higher internalizing and externalizing behavior scores. A lower nonverbal cognition score was also associated with higher internalizing behavior scores but to a lesser extent than RRB. These findings suggest that SLPs may support internalizing and externalizing behaviors in autistic children by taking RRBs and nonverbal cognition into consideration.